Estate Planning “Need to Knows” for Military Families - Barbara O'Neill; Martie Gillen; Kristen Jowers (EDIS)
This publication discusses general information about estate planning, military-specific estate planning, five estate planning tips for military families, and estate planning resources. Written by Barbara O’Neill, Martie Gillen, and Kristen Jowers, and published by the UF/IFAS Department of Family, Youth and Community Sciences, January 2024.